Perovskite Nanowires: Semimetallicity and Negative Differential Resistance from Hybrid Halide Perovskite Nanowires (Adv. Funct. Mater. 13/2019). (26th March 2019) - Khan, Muhammad Ejaz; Lee, Juho; Byeon, Seongjae; Kim, Yong‐Hoon
Abstract : In article number 1807620, Yong‐Hoon Kim and co‐workers show that the PbI3 nanowire, the inorganic framework of trimethylsulfonium lead triiodide (TMSPbI3 ) perovskite, assumes a semi‐metallic character, and displays excellent negative differential resistance (NDR) characteristics emerging from the PbI3 ‐TMSPbI3 ‐PbI3 junctions through the novel quantum‐hybridization NDR mechanism.